Physical Activity and the Glymphatic System: Potential Interactions and Implications for Brain Health - Makulec, Gabriela; Domosud, Karolina; Zienkiewicz, Damian; Ostaszewska, Magdalena; Walendziak, Weronika; Mordal, Natalia; Ściebura, Kacper; Wiśniewska, Wiktoria; Majchrzyk, Milena; Malczyk, Anna (Quality in Sport, 2026)
Background: The glymphatic system is a perivascular network that promotes the exchange of cerebrospinal fluid (CSF) and interstitial fluid (ISF) and assists the elimination of metabolic waste products from the central nervous system. Aim: The aim of this narrative review was to summarise current evidence regarding possible interactions between physical activity and glymphatic function. Methods: A literature search was conducted in PubMed to identify studies addressing glymphatic transport, CSF dynamics, and physiological adaptations associated with exercise. Results: The majority of research on the effect of exercise on the glymphatic system is from experimental studies using animal models, which have found that voluntary exercise is associated with increased influx and clearance of interstitial solutes. These effects have also been linked to improved vascular health, decreased neuroinflammation, alterations in aquaporin-4 polarisation, and improved sleep health, including increased slow-wave sleep. Recent neuroimaging findings in human research suggest that long-term physical activity is connected with increased MRI measurements of glymphatic and meningeal lymphatic flow. Conclusions: These findings are all derived from indirect imaging methods, and many studies indicate that physical activity affects multiple physiological pathways involved in glymphatic transport. Further studies combining exercise interventions with advanced neuroimaging approaches are needed to clarify whether and how physical activity influences glymphatic function in the human brain.